'Why didn't we think to do this earlier?' Chemists thrilled by speedy atomic structures. (1st November 2018) - Warren, Matthew
Cross-disciplinary thinking was key to realizing the potential of electron diffraction to organic chemistry. Chemists thrilled by speedy atomic structures Cross-disciplinary thinking was key to realizing the potential of an existing technique to resolving structure of tiny organic molecules. Polarised LM of crystals of the drug paracetamol